SELF-THERAPY AS A FORM OF COPING WITH STRESS - Wiesława PACHOLEC (Association of Social and Educational Innovation, 2024)
Stress is an integral part of our lives. It can be our friend, but also our enemy. It is important to be able to cope with it on a daily basis, but also in difficult situations. Self-therapy is one of the effective forms of coping with stress